Developing a Sound, Noise and Health Conceptual Framework for fair and equitable dispersion of aircraft - Lavia, Lisa R.; Clark, Charlotte; Torija, Antonio J. (Frontiers in Acoustics, 2025)
Agreed Fair and Equitable Dispersion of aircraft is an aspirational objective by many airports to alleviate the burden of noise from aircraft/airspace changes on affected communities and a hot topic in aviation generally. A workable definition of Fair and Equitable Dispersion would, in theory, enable airspace managers and aircraft operators to design solutions to deliver quicker, quieter and cleaner journeys and more capacity for the benefit of those who use and are affected by airspace. However, reaching consensus amongst stakeholders on an agreed definition of Fair and Equitable Dispersion is highly challenging and not just a technical issue due to the substantial acoustic, health, quality of life and non-acoustic factors affecting the human perceptual response to sound in context. This paper presents findings from an independent study in the United Kingdom aimed at developing a definition of an airport’s Fair and Equitable Distribution of traffic and recommendations to inform stakeholder discussions as a stage process. To the best of the authors’ knowledge, this was the first study of its kind in the UK with this aim. Using a mix of descriptive and exploratory qualitative research techniques, the study compiles findings from reviews of aviation noise metrics, policy and technology options; an updated evidence review of health effects of aircraft noise; and an overview of the impact of non-acoustic factors. The study proposed a transdisciplinary Sound, Noise and Health Conceptual Framework and recommendations for implementation as a stage process comprised of: i locally salient non-acoustic factors derived and mapped through stakeholder engagement, ii a Health Dashboard incorporating agreed combined environmental and health metrics, iii acoustic and psychoacoustic metrics building upon a perception-based engineering approach, iv operational indicators to be agreed with local and national stakeholders, within the international context. The study posits important considerations for future air transport policy and sound, noise and health research and sets a foundation for further ongoing studies to apply the proposed Sound, Noise and Health Conceptual Framework.